2007
DOI: 10.1038/sj.npp.1301499
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Donepezil in Patients with Schizophrenia or Schizoaffective Disorder: Significant Placebo/Practice Effects in a 12-Week, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Altered expression of central muscarinic and nicotinic acetylcholine receptors in hippocampal and cortical regions may contribute to the cognitive impairment exhibited in patients with schizophrenia. Increasing cholinergic activity through the use of a cholinesterase inhibitor (ChEI) therefore represents a possible strategy for cognitive augmentation in schizophrenia. We examined the efficacy and safety of the ChEI donepezil as cotreatment for mild to moderate cognitive impairment in schizophrenia or schizoaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 73 publications
3
93
0
2
Order By: Relevance
“…Likewise, most RCTs investigating ChEIs include fewer than 30 patients (only one included 245 patients; otherwise, fewer than 90 were included). However, this should not be the case with ChEIs given that the study conducted by Keefe and colleagues [25] had a sufficient sample even though they found that donepezil was less effective than was placebo. The study conducted by Buchanan and colleagues [28] was also moderately powered, but only a few post hoc analyses found significant results.…”
Section: Interpretation Of Currently Available Data and Future Researmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, most RCTs investigating ChEIs include fewer than 30 patients (only one included 245 patients; otherwise, fewer than 90 were included). However, this should not be the case with ChEIs given that the study conducted by Keefe and colleagues [25] had a sufficient sample even though they found that donepezil was less effective than was placebo. The study conducted by Buchanan and colleagues [28] was also moderately powered, but only a few post hoc analyses found significant results.…”
Section: Interpretation Of Currently Available Data and Future Researmentioning
confidence: 99%
“…In fact, the joint academic and industry initiative known as Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) has developed guidelines and proposed the use of a cognitive battery (MCCB) addressing seven cognitive domains (speed of processing, attention/ vigilance, working memory, verbal learning, visual learning, reasoning and problem solving, and social cognition) to improve the specificity of treatments for cognitive deficits [29]. Although the study conducted by Keefe and colleagues investigating donepezil [25] was designed and initiated before the establishment of the MATRICS guidelines and the MCCB, their study was consistent with these recommendations and may be considered representative of rigorous research in this field. Although the MCCB has excellent reliability, minimal practice effects, and significant correlations with measures of functional capacity, its sensitivity to changes during pharmacological treatment has yet to be confirmed [30].…”
Section: Interpretation Of Currently Available Data and Future Researmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, evidence suggests use of donepezil in schizophrenia yields no effect (Keefe et al, 2008), while galantamine seems to improve some cognitive domains Lee et al, 2007;Schubert et al, 2006), particularly in combination with antipsychotics; however evidence is still weak due to the limitations of included studies (Singh et al, 2012). Similarly, a systematic review (Zdanys and Tampi, 2008) did not find conclusive results for the use of memantine in several psychiatric disorders, including depression, schizophrenia, obsessive-compulsive disorder, substance abuse, pervasive developmental disorders, and binge eating disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there exists no information on the long-term effects on cognition. In addition, the studies show that there are little differences in terms of cognitive-enhancement even compared to placebo: one study [152] even showed a better cogni tive improvement in the placebo group. In addition, many of the CE drugs are most effective only on patients characterized by the lowest baseline of cognitive performance [153][154][155][156][157], while even impairing performance of patients with high baseline cognitive function [154,[158][159][160][161].…”
Section: Summary Of Desired Effects and Side Effects Of Drugs For Cementioning
confidence: 99%